Should Chlamydia trachomatis confirmation make you cross? Performance of collection kits tested across three nucleic acid amplification test platforms. Issue 4 (28th July 2006) - Scragg, S; Bingham, A; Mallinson, H
Abstract : Objective: To investigate the feasibility of confirming initially reactive nucleic acid amplification assays for Chlamydia trachomatis (CT) by cross testing on a second molecular platform. The three platforms investigated were Aptima Combo 2 assay (AC2), Cobas Amplicor CT test (PCR) and ProbeTec ET CT assay (SDA). Methods: Serial dilutions of a CT culture were prepared in 0.9% saline; used to prepare simulated swab samples for all three platforms, and tested as in the manufacturer's instructions. For the cross testing investigation, 1 ml of the simulated swab samples prepared in each of the three collection kits was transferred into the appropriate collection kit for the second platform. Results: AC2 demonstrated a higher analytical sensitivity than the SDA and PCR assays. Upon cross testing AC2 again demonstrated a superior performance to the SDA and PCR assays even when testing swab samples originally prepared in the SDA and PCR transport medium. The SDA assay was inhibited by the addition of transport medium from both the AC2 and PCR assays. Conclusion: The analytical sensitivity of the three assays is not identical, therefore confirming initially reactive samples on a second platform may prove to be difficult. However, the higher sensitivity of the AC2 assay could allow its use as a confirmatory assay for reactive swab samples collected in the SDA and PCR transport medium.